1974
DOI: 10.3758/bf03198154
|View full text |Cite
|
Sign up to set email alerts
|

Single-trace fragility theory of memory dynamics

Abstract: In single-trace fragility theory, forgetting is produced by two factors, time and interference. Memory traces are assumed to have two partially coupled dynamic properties, strength and fragility. Strength determines the probability of correct recall and recognition, while fragility determines the susceptibility of the trace to the time-decay process but not to the interference process. Consolidation is assumed to be a continual reduction in the fragility of the memory trace rather than any change in strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
206
2
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(214 citation statements)
references
References 15 publications
5
206
2
1
Order By: Relevance
“…To the data, Wetzler and Sweeney fitted a power function that in many investigations (e.g., Crovitz & Schiffman, 1974;Rubin & Wenzel, 1996;Rubin, Wetzler, & Nebes, 1986) has been shown to capture the distribution of memories across the life span. As discussed by Rubin and Wenzel (1996), the power function (e.g., Wickelgren, 1974Wickelgren, , 1975 implies that equal ratios of time (t 1 /t 2 Ï­ t 3 /t 4 ) will result in equal ratios of recall (recall 1 /recall 2 Ï­ recall 3 /recall 4 ). Thus, for example, if Time 2 recall was 90% of Time 1 recall, then Time 4 recall would be 90% of Time 3 recall (i.e., assuming equal ratios of time).…”
Section: Characteristic Distribution Of Early Memoriesmentioning
confidence: 99%
“…To the data, Wetzler and Sweeney fitted a power function that in many investigations (e.g., Crovitz & Schiffman, 1974;Rubin & Wenzel, 1996;Rubin, Wetzler, & Nebes, 1986) has been shown to capture the distribution of memories across the life span. As discussed by Rubin and Wenzel (1996), the power function (e.g., Wickelgren, 1974Wickelgren, , 1975 implies that equal ratios of time (t 1 /t 2 Ï­ t 3 /t 4 ) will result in equal ratios of recall (recall 1 /recall 2 Ï­ recall 3 /recall 4 ). Thus, for example, if Time 2 recall was 90% of Time 1 recall, then Time 4 recall would be 90% of Time 3 recall (i.e., assuming equal ratios of time).…”
Section: Characteristic Distribution Of Early Memoriesmentioning
confidence: 99%
“…In particular, Donkin and Nosofsky (2012a) conducted a short-term proberecognition experiment involving the sequential presentation of memory-set items. In modeling the choice and RT data from that experiment, Donkin and Nosofsky (2012a) obtained evidence that the "memory strength" of the items decreased as a power function of their lag of presentation (see also Anderson & Schooler, 1991;Wickelgren, 1974;Wixted & Ebbesen, 1991). In the context of the present types of visual WM tasks, one might imagine an analogous process in which the observer shifts covert visual attention across the memoryset items, with more recently attended items having greater memory strength.…”
Section: Extensions To Continuous Shared-resources Modelsmentioning
confidence: 99%
“…Reed (1977) showed that the Markov model of Young (1971) performed more or less similar as the present model (leading to a χ 2 -value of 49.3, df = 18). However, a model based on Wickelgren's strength-resistance theory (Reed, 1976;Wickelgren, 1972Wickelgren, , 1974aWickelgren, , 1974b) did perform substantially better, leading to χ 2 values between 24 and 30 depending on the exact assumptions of the model. The basic reason for this superior fit seems to be due that the Reed model is capable of fitting the initial decrease for short retention intervals when the spacing interval increases from 0 to 3 s (see the top curve in the left panel of Fig.…”
Section: Fits To Standard Data On Spacingmentioning
confidence: 99%